From Co-Learning to Shared Commitment to Agroecology. Some Insights from Initiatives Aimed at Reintroducing Agrobiodiversity - Adanella Rossi (Sustainability, 2020)
Agroecology represents a holistic approach in the transition to food system sustainability, integrating different dimensions, including knowledge creation, practices redefinition and social mobilisation. This study aims to explore the processes underlying the implementation of the agroecological approach and its transformative potential, focusing on the learning processes that lead to the development of new, shared systems of knowledge, values and beliefs, and to the growth of reflexivity and agency. It aims at deepening the understanding of these processes by analysing the reintroduction of agrobiodiversity in crop/food systems, considering this as a founding element of the agroecological model. Three initiatives located in Italy are investigated to that end. The study analyses role, mechanisms and potential of co-learning processes that develop within the multi-actor networks involved, uncovering enabling and hindering factors. It focuses on the role, reciprocal articulation and cumulative effects of three elements: actors involved and ways of interacting, types of knowledge mobilised and facilitation actions carried out. The findings highlight that the factors ensuring effectiveness of mutual learning, such as modes of actor interaction and, particularly, facilitation, are crucial. At the same time, the mechanisms that intervene seem increasingly complex, showing the need for deeper research and adequate forms of support.